Reversal of spin-polarization near the Fermi level of the Rashba semiconductor BiTeCl - J. Qu; X. Han; S. Sakamoto; C. J. Jia; J. Liu; H. Li; D. Guan; Y.-J. Zeng; M. Schüler; P. S. Kirchmann; B. Moritz; Z. Hussain; et al. (npj Quantum Materials, 2023)
Abstract Spin–orbit coupling forms the physical basis for quantum materials with non-trivial topology and potential spintronics applications. The Rashba interaction is a textbook model of spin–orbit interactions, with charge carriers undergoing linear, isotropic spin-splitting in momentum space. Recently, non-centrosymmetric semiconductors in the family BiTeX (X = Cl, Br, I) have been identified as exemplary Rashba materials due to the strong splitting of their bulk bands, yet a detailed investigation of their spin textures, and their relationships to local crystal symmetry, is currently lacking. We perform high-efficiency spin-resolved photoemission spectroscopy to directly image the spin texture of surface states of BiTeCl, and we find dramatic deviations from idealized behavior, including a reversal of the spin-polarization near the Fermi level. We show that this behavior can be described by higher-order contributions to the canonical Rashba model with the surface states localized to individual trilayers of the crystal. Due to the prominence of these effects near the Fermi level, they should have a strong impact on the spin-dependent transport of carriers.